U-Pb geochronology and geochemistry from the northeastern New River belt, southern New Brunswick, Canada: significance of the Almond Road Group to the Ganderian platformal margin - Johnson, Susan C.; Dunning, Gregory R.; Miller, Brent V. (Atlantic Geoscience, 2018)
The Almond Road Group in the northeastern New River belt comprises two formations: the basal Snider Mountain Formation contains orthoquartzite, feldspathic quartzite, and quartzite pebble conglomerate; the gradationally overlying Ketchum Brook Formation is composed of feldspathic sandstone, laminated dark siltstone and shale, overlain by mafic lithic tuffs and basaltic flows. The Almond Road Group overlies latest Ediacaran to earliest Cambrian (early Fortunian) pyroclastic, volcaniclastic, and epiclastic rocks of the Belleisle Bay Group. Based in part on this relationship, the Almond Road Group was thought to be Early Cambrian, although an upper age limit had never been determined. A U–Pb (zircon) age of 475 ± 2 Ma for the West Scotch Settlement porphyry, a small felsic hypabyssal intrusion emplaced into the Ketchum Brook Formation, demonstrates that the Almond Road Group is no younger than Early Ordovician (early Floian) age. Its age is further constrained by LA ICP-MS detrital zircon data from a basal quartzite in the Snider Mountain Formation. Results show a dominant peak in the Ediacaran (ca. 575 Ma), with the youngest coherent cluster of ages at ca. 530–520 Ma. Together these data support a Cambrian age for the quartz-rich Almond Road Group and its platformal relationship to Ganderia.